Analysis of Factors Affecting Nurse Performance in DKT Hospital Kediri Hospital - Eko Lulus Budiyanto (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Various complaints from the public regarding the performance of services in hospitals must be cared for by the managers and organizers of hospital services and while the factors that affect performance are satisfaction, compensation and the organization's environment. The general objective of this research is to analyze the influence of factors of satisfaction, compensation and organizational climate on the performance of nurses in the DKT Hospital of Kediri City. The research design used was cross sectional with questionnaire sheet instruments. The population of this study was 90 nurses. Samples were 74 using random sampling techniques, while to determine the effect between variables used ordinal regression test with a significant level of 0.05. Based on the results of the study, it was found that the organizational climate in the good category was 40 respondents (54.1%), compensation in the good category was 38 respondents (51.4%), had satisfaction in good categories as many as 54 respondents (73%), and performance in the category good as many as 48 respondents (64.9%). The results of data analysis showed the factors that most influence performance is the organizational climate with p value 0.003. Every nurse gets the opportunity to be able to carry out their duties as well as possible so that they have high motivation in working and increasing their productivity. And if the organization's organizational climate is able to build team spirit like this, then by itself it will support the creation of a conducive climate to support nurses performance